EFFECT OF STORAGE ON SOME BIOCHEMICAL PARAMETERS OF SELECTED FRESH FRUITS JUICE - SUSHMA; MOHD. ARIF KHAN; MANISH KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Juices of five selected fruits (orange, mango, apple, grape and pomegranate) were subjected to evaluate of some biochemical parameters on storage. Among all fresh juices studied mango was found to have highest total sugar content (14.8±0.08 g/100ml) as well as pH (4±0.04), orange and pomegranate were found to have high acidity (0.97±0.06 g/100g) whereas vitamin-C was found in higher concentration in orange (20±0.23 mg/100ml). There was only a small change in all the biochemical parameters studied on storage up to the period of 4 hrs.